Prevalence and Determinants of Stress among University Students in Bangladesh: Insights from a Study at Gopalganj Science and Technology University - Hossain, Mohammad Kamal; Halder, Arpita (International Journal of Statistical Sciences, 2025)
Stress is a significant mental health concern among university students globally, yet research in Bangladesh often addresses it alongside other mental health issues, leaving stress-specific insights underexplored. This study focuses on stress as an independent factor, examining its prevalence and the associated determinants among students at a Bangladeshi university. A cross-sectional survey was conducted among 384 students from Gopalganj Science and Technology University, Gopalganj, Bangladesh, using the BDASS-21 scale to measure stress levels. To ensure a representative sample, the researchers employed a stratified random sampling technique. Chi-square and two-sample t-tests were employed to assess the relationship between stress levels and independent variables. A logistic regression model identified significant predictors of stress, with a 5% level of significance applied to determine statistical relevance. The prevalence of stress was 62.50% among the surveyed students. Logistic regression analysis revealed several significant predictors of stress. Students from joint families were found to be four times more likely to experience stress (OR = 4.05, 95% CI: 1.43–11.42, p = 0.01) compared to those from nuclear families. Engagement in a relationship (OR = 3.91, 95% CI: 1.28–11.99, p = 0.02) and smoking habits (OR = 4.51, 95% CI: 1.46–13.92, p = 0.01) were also associated with elevated stress levels. Additionally, lack of physical exercise and dissatisfaction with social life were significant contributors to stress. Over half of the university students in this study reported experiencing stress, with higher risks observed among those engaged in relationships, from joint families, and with smoking habits. Targeted interventions addressing these high-risk groups, including promoting healthy lifestyles and social support, are recommended for policymakers and university authorities to mitigate stress and improve student well-being. IJSS, Vol. 25(1), March, 2025, pp 23-37